Kelayakan E-Book Berbasis Digital Berbantuan Budaya Materi Teks Anekdot Kelas X SMK Madani Marindal I - Sarah, Fatimah; Safina, Nila; Kartika, Rika (Medan Resource Center, 2025)
The purpose of this study was to develop e-books and assess their feasibility in teaching anecdote texts to tenth-grade students at SMK Madani Marindal I. The research population consisted of 65 students from the X TKJ class, with a sample of 35 students selected for the study. This research employed the Research and Development (R&D) method using the Borg and Gall model, which comprises seven stages: research and data collection, planning, product draft development, initial trials, field trials, refinement of the initial product, further field trials, and final product refinement. Data were collected through a questionnaire, employing observation, interviews, and survey techniques. The results of this study are expected to contribute to the improvement of learning materials through digital platforms, enhancing students’ engagement and comprehension of anecdote texts. The findings will also provide insights into the effectiveness of e-books as an alternative instructional medium in vocational high schools.